Development of mathematical competence as a key competence in English language teaching - A. Neguliaieva (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The relevance of the study is conditioned to the need to explore new effective methods of implementing competence-oriented education while teaching English and forming key competences as a basis for learners’ comprehensive development and successful integration into a fast-moving cross-cultural society. The purpose of the study was to substantiate the category “mathematical competence in English language teaching learning” and analyse the survey of English language teachers to determine its understanding among teachers of secondary educational institutions. General scientific and empirical methods, deduction, comprehensive analysis, and comparison facilitated achieving the set goals. Hence, this paper presents the research on implementing the competence-oriented strategy stated by the Law of Ukraine on Education in general and the features of developing mathematical competence in English language teaching/learning as a key one. The modern view on understanding the concept in scientific discourse was analysed, including considering mathematical competence as a subject-specific, key, and super-competence. Assuming that communication is one of the methods and ways of teaching the English language, the authors’ vision of its definition regarding its development in the language learning was suggested. In addition, the survey of English language teachers was conducted and analysed and contradictions and problems in its comprehension and implementation among teachers were revealed: understanding the need to develop mathematical competence as a key one in teaching English; and the lack of methods and didactic materials for practical use at the English language lessons at secondary educational institutions. Furthermore, outlined prospects for future research in developing methods and efficient didactic materials for developing the mentioned competence and conducting an experiment to prove their effectiveness. These didactic materials also should comprise the psychological, linguistic, and lingua-didactic aspects, previously substantiated by the author of this paper, for developing mathematical competence as a key one in the process of teaching the English language